1994
DOI: 10.1161/01.hyp.24.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Is nitric oxide involved in the tonic inhibition of central sympathetic outflow in humans?

Abstract: Recent studies in experimental animals have advanced the concept that neuronal nitric oxide is an important component of the signal transduction pathways that tonically restrain sympathetic vasoconstrictor outflow from the brain stem. To determine whether or not this concept can be extended to the control of sympathetic outflow in humans, we recorded muscle sympathetic nerve activity (microelectrodes, peroneal nerve) in healthy human subjects during intravenous infusion of the nitric oxide synthase inhibitor N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
3
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 35 publications
5
76
3
1
Order By: Relevance
“…35 We infused L-NMMA intravenously at a dose that has been shown to increase blood pressure and activate the baroreflex and to effectively block eNOS and nNOS in experimental animals 36 and humans. 14,37 Given that the coronary circulation extracts Ϸ5% of cardiac output, with our systemic doses of L-NMMA we would expect to achieve coronary concentrations of Ϸ50 mol (group 2) and 164 mol (groups 3 and 5), respectively, which compare well with the figures of 32, 30 125, 2 and 320 mol 3 shown to block coronary eNOS when administered via an intracoronary route. Thus, it is reasonable to assume that with our high-dose L-NMMA infusion, we have successfully blocked a substantial amount of both eNOS and nNOS.…”
Section: Kaufmann Et Al Neural Constraint Of Maximal Myocardial Bloodmentioning
confidence: 52%
See 1 more Smart Citation
“…35 We infused L-NMMA intravenously at a dose that has been shown to increase blood pressure and activate the baroreflex and to effectively block eNOS and nNOS in experimental animals 36 and humans. 14,37 Given that the coronary circulation extracts Ϸ5% of cardiac output, with our systemic doses of L-NMMA we would expect to achieve coronary concentrations of Ϸ50 mol (group 2) and 164 mol (groups 3 and 5), respectively, which compare well with the figures of 32, 30 125, 2 and 320 mol 3 shown to block coronary eNOS when administered via an intracoronary route. Thus, it is reasonable to assume that with our high-dose L-NMMA infusion, we have successfully blocked a substantial amount of both eNOS and nNOS.…”
Section: Kaufmann Et Al Neural Constraint Of Maximal Myocardial Bloodmentioning
confidence: 52%
“…4,40 -42 It remains controversial whether inhibition of nNOS elicits sympathoexcitatory effects 14 or not, 37 because it may exert opposing effects at different sites. 43 The present study is the first to report a net increase in adenosineinduced hyperemic MBF in response to L-NMMA.…”
Section: Kaufmann Et Al Neural Constraint Of Maximal Myocardial Bloodmentioning
confidence: 99%
“…It is not clear, however, how important this mechanism is in restraining BP in humans; studies in favor and against this possibility can be found in the literature. In some studies, the increase in BP produced by systemic administration of L-NMMA is accompanied by a similar reflex decrease in muscle sympathetic nerve activity to that produced by an equipressor dose of phenylephrine (3,8), suggesting that NO does not tonically restrain central sympathetic outflow in humans. Other studies have reached the opposite conclusion; in one study, NOS inhibition increased BP but did not produce the expected baroreflex-mediated decrease in sympathetic nerve activity (15); in another, the increase in BP induced by NOS inhibition was partially reversed by the ␣-adrenergic antagonist phentolamine (21).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the increase in blood pressure produced by systemic administration of the NOS inhibitor N G -monomethyl-L-arginine (L-NMMA) results in a reflex decrease in muscle sympathetic nerve activity 5 that is similar to that produced by an equipressor dose of phenylephrine, suggesting that NO does not tonically restrain central sympathetic outflow in humans. 6 On the other hand, in other studies, NOS inhibition with N G -nitro-L-arginine methylester resulted in a larger increase in blood pressure that was partially reversed with the ␣-adrenergic antagonist phentolamine, most likely reflecting a tonic inhibition of sympathetic tone by nNOS. 7 The relative contribution of endothelial-derived NO to blood pressure, therefore, remains difficult to assess.…”
mentioning
confidence: 89%